1996
DOI: 10.1046/j.1365-2141.1996.d01-1789.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemopoietic growth factor tyrosine kinase receptor expression profiles in normal haemopoiesis

Abstract: Expression profiles were generated for the haemopoietic tyrosine kinase receptors (HGF-TKRs or class III TKRs) by PCR on cDNA samples (RT-PCR) using a degenerate primer set. Each profile consisted of primary and secondary, i.e. enriched for less-expressed sequences, fingerprints. This method was applied on FACS-purified haemopoietic CD34+ cells, both from bone marrow (BM) and umbilical cord blood (UCB), and on mature cells from peripheral blood. CD34+ BM cells showed expression of c-fms. flt3, whereas CD34+ UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 14 publications
6
15
1
Order By: Relevance
“…In contrast, the in vitro effects of FLT3L on mature peripheral blood cells have received less attention (41). It is believed that FLT3 expression is confined mainly to progenitor cells, and its expression has not been observed in monocytes in the physiological condition (8)(9)(10). In accordance with these previous reports, we did not detect expression of FLT3 in purified peripheral monocytes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In contrast, the in vitro effects of FLT3L on mature peripheral blood cells have received less attention (41). It is believed that FLT3 expression is confined mainly to progenitor cells, and its expression has not been observed in monocytes in the physiological condition (8)(9)(10). In accordance with these previous reports, we did not detect expression of FLT3 in purified peripheral monocytes.…”
Section: Discussionsupporting
confidence: 78%
“…As previously reported (8)(9)(10)(11), no detectable FLT3 expression was observed in peripheral blood CD14 + monocytes by flow cytometry. (Fig.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…RT ± PCR results could be in¯uenced by c-ret mRNA contamination from stromal cells, lymphocytes (Visser et al, 1996), or parafollicular C-cells in normal thyroid tissue. These sources of ret transcripts are, however, unlikely as an explanation for the observed cret mRNA in papillary carcinomas since in situ hybridization did not show evidence of ret mRNA expression in lymphocytes or stromal cells (Lam et al, The notation of two temperatures (e.g.…”
Section: Wild-type C-ret Mrna and Protein In Ptcmentioning
confidence: 99%
“…the glial cell line-derived neurotrophic factor (GDNF) (Jing et al, 1996;Treanor et al, 1996) and the neurturin (NTN) (Kotzbauer et al, 1997). Recent studies have shown that GDNF-and NTN-dependent RET signalling requires the presence of either one of two related glycosyl-phosphatidylinositol (GPI)-linked cell surface-associated co-receptors, respectively termed GDNFR-a (Jing et al, 1996;Treanor et al,Although first described as a non-haemopoietic RTK involved in the physiologic development of neural crest derivatives, enteric nervous system and components of the excretory system Pichel et al, 1996;Sanchez et al, 1996), previous studies from our and other groups (Visser et al, 1996;Gattei et al, 1997a) have demonstrated the expression of the RET RTK in human normal and malignant haemopoietic cells. In particular, RET mRNA, expressed at a low level in normal CD34 þ haemopoietic progenitors, has been found to increase upon differentiation to mature myelomonocytic cells, being maximal in circulating neutrophils and monocytes (Visser et al, 1996;Gattei et al, 1997a).…”
mentioning
confidence: 99%